174k views
1 vote
Y= 9x + 7 over 3 rewrite in standard form

User Simap
by
4.9k points

2 Answers

0 votes
subtract 9x from its side and move it over, -9x+y=7/3 should be your answer, hope i helped
User Chris Stillwell
by
5.0k points
6 votes

Answer:


3x-1y=-(7)/(3)

Explanation:

We've been given the equation
y=(9x+7)/(3)

In order to bring it in the standard form we must write it as Ax + By = C

First, we need to split and divide both the terms of the numerator by 3 on the right side


y=(9x)/(3)+(7)/(3)

Simplifying
(9)/(3), we get 3


y=3x+(7)/(3)

Subtract
(7)/(3) from both side


y-(7)/(3)=3x+(7)/(3)-(7)/(3)

Cancel out
+(7)/(3) and
-(7)/(3) from the right side


y-(7)/(3)=3x

Subtract y from both sides


y-(7)/(3)-y=3x-y

Cancel out y and -y on the left side


-(7)/(3)=3x-y

y is written as 1y


-(7)/(3)=3x-1y

Flip the sides


3x-1y=-(7)/(3)

User Shivam Agrawal
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.